Diversity in income-generating activities for sedentarized pastoral women in northern Kenya - Nduma, I.; Kristjanson, Patricia M.; McPeak, J.G. (2001)
As East African pastoralists settle around market centers, women often adopt new town-based activities to generate income. While settling in or near towns presents women with new opportunities, household poverty may prevent them from exploiting these opportunities or lead them to adopt environmentally unsustainable survival strategies that contribute to the localized degradation of the natural resource base. A survey of 102 Rendille women in and around Korr town in Marsabit District of northern Kenya was undertaken to understand their income-generating strategies. Strategies analyzed in this study are the sale of milk, based on pastoral production; the collection and sale of firewood, which may be environmentally unsustainable; and income generation through small-scale trading, which has become increasingly important as market integration increases in northern Kenya. The results show that Korr women are by no means all pursuing the same income-generating activities. Potential poverty-alleviation strategies include emphasis on research and investments aimed at improvements in milk marketing opportunities and efficiencies, increasing regional employment opportunities, strengthening collective action by pastoral women, and increasing their level of participation in decision making aimed at sustainable use of natural resources.